Revolutionizing microplastic detection in water through quantum dot fluorescence - Sreedevi Paramparambath (17346997) (2025)
Microplastics (MPs) are emerging environmental contaminants that pose significant risks to ecosystems and human health. Traditional detection methods for microplastics in water and other matrices often involve complex and costly techniques. In this research, we introduce an innovative approach utilizing carbon quantum dots (CQDs), a class of fluorescent nanomaterials known for their simple synthesis, low cost, eco-friendliness, and low toxicity. MPs were successfully stained with CQDs by optimizing the reaction conditions through a microwave-assisted synthesis. The resulting MP-CQD composites were characterized using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), profilometry, and UV–Vis analysis. This study further investigated the fluorescence emission from CQD-stained MPs and examined the impact of MP concentration on particle agglomeration. This novel method demonstrated the ability to effectively agglomerate and detect MPs at very low concentrations, offering a streamlined and efficient approach to MPs detection in water. The optimized method enabled visible fluorescence detection of MPs at concentrations as low as 0.005 ppm, demonstrating sensitivity comparable to instrumental approaches but with greater simplicity and accessibility. The integration of CQDs into this process marks a significant advancement in detecting and potentially removing MPs from aquatic environments. Other Information Published in: Journal of Environmental Science and Health, Part A License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/10934529.2025.2578105